Which Contributes to Clinical Performance: Academic Output or Person-Environment Fit? - Minye Dong; Minye Dong; Yuyin Xiao; Yuyin Xiao; Chenshu Shi; Chenshu Shi; Wu Zeng; Fan Wu; Guohong Li; Guohong Li (Frontiers Media S.A., 2022)
BackgroundThe measures put in place by health authorities to ensure the professionalism of doctors are important. Hospitals in China have included academic outputs in the promotion criteria to incentive medical clinicians to engage in scientific research so that to improve job performance (JP). However, such practice disproportionally focuses on academic outputs but ignores the force of needs fulfilled brought by intrinsic incentive. This study aims to discuss the realistic problem regarding the promotion mechanism and the potential drivers to clinical JP.MethodsThis study was based on multi-source data collection on clinical performance from electric medical record (EMR), person-environment (P-E) fit from the survey, and academic output from personnel files of ward clinicians (n = 244) of general public hospitals who sought for career progression in Shanghai in 2020. Independent-Sample t-test and chi-square test were used for comparison of two sample means or constituent ratio between promoted and not promoted clinicians. Linear multilevel regression was conducted to examine the relationship between clinical performance and academic outputs and P-E fit.ResultsClinicians who were promoted were more productive in producing academic outputs than those who were not (t = −5.075, p < 0.001). However, there was no difference in clinical performance between the two groups (t = −1.728 to 0.167, p > 0.05). The regression showed that academic outputs were not related to clinical performance, while higher P-E fit was associated with the improvement of various clinical performances.ConclusionThis study shows that P-E fit plays a more important role in facilitating clinical performance than academic performance and highlights the importance of intrinsic motivation of clinicians in achieving clinical performance.